Microbial naringinase: from microbial source to its current applications in various fields - Golgeri M, Dilshad Begum; Mulla, Sikandar I.; Bagewadi, Zabin K; Faniband, Basheerabegum; Mishra, Prabhakar; Bankole, Paul Olusegun; Sharma, Swati; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Bharagava, Ram Naresh; Romanholo Ferreira, Luiz Fernando (Springer Nature, 2025)
Naringinase is a multifunctional enzyme well known for debittering. Naringinase has been used for processing of citrus fruits in industry. Moreover, it exhibits dual activities that catalyze hydrolysis of α-rhamnose as well as β-glucose from naringin (a flavanone). In this review, we aimed to provide detailed information related to the research works carried out on naringinase enzyme. The effort has been primarily made to emphasize the microbial sources, characterization of the enzyme, strategies adopted for enhanced naringinase production along with its broad applications in various filed. This review will be helpful to nutritional biochemists and enzymologists involved in environmental management. Future work can be focused on computation-based research (including molecular docking and molecular dynamics simulations) on naringinase which is currently not well known and will be added source to improve production and utilization of this enzyme in different sectors.
Keywords: Characterization and Application; Naringenin; Naringin; Naringinase; Production